2020
DOI: 10.1017/s1047951120003741
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and congenital heart disease: an insight of pathophysiology and associated risks

Abstract: Objective: We aimed to examine the literature to determine if both paediatric and adult patients diagnosed with congenital heart disease (CHD) are at a higher risk of poor outcomes if they have the coronavirus disease 2019 (COVID-19), compared to those without CHD. Methods: A systematic review was executed using the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines. To identify articles related to COVID-19 and CHD, an extensive literature search was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 52 publications
0
27
0
3
Order By: Relevance
“…18 In the same context, a systematic review by Haiduc et al has included concluded that CHD increases the risks of bad outcomes for patients infected with COVID-19. 15 On the contrary, an Italian multi-centre, observational cohort study that included 76 CHD patients that acquired COVID-19 infection has observed a mild clinical course of COVID-19 symptoms in CHD patients. 19 Another study included six neonates with CHD that were born to mothers diagnosed with w SARS-CoV-2 during their pregnancy showed that all six neonates were not infected or suffer from any adverse effect.…”
Section: Impact Of Covid-19 On Chd Patientsmentioning
confidence: 98%
See 2 more Smart Citations
“…18 In the same context, a systematic review by Haiduc et al has included concluded that CHD increases the risks of bad outcomes for patients infected with COVID-19. 15 On the contrary, an Italian multi-centre, observational cohort study that included 76 CHD patients that acquired COVID-19 infection has observed a mild clinical course of COVID-19 symptoms in CHD patients. 19 Another study included six neonates with CHD that were born to mothers diagnosed with w SARS-CoV-2 during their pregnancy showed that all six neonates were not infected or suffer from any adverse effect.…”
Section: Impact Of Covid-19 On Chd Patientsmentioning
confidence: 98%
“…12 For that, the management of CHD patients and the impact of COVID-19 on them makes a challenge for the health care system. [13][14][15] Bertoncelli et al outlined that the outcome of COVID-19 infection can vary according to the type of CHD. He also categorized the high-risk patients which include large ventricular septal defect (VSD), tricuspid atresia, and hypoplastic left heart syndrome.…”
Section: Covid-19 and Congenital Heart Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is limited amount of data as to which factors related to ACHD are prognostic for COVID-19 increased severity and is hard to predict clinical outcomes 7 . However, amidst the pandemic, the need for intensive follow-up of ACHD patients, no matter if their clinical condition is deemed stable, persists 8 .…”
Section: Correspondencementioning
confidence: 99%
“…In our systematic review of current published literature, we have reported outcomes on 12 papers; five of them were cases reports, four case series and three cross-sectional studies totalling 143 patients, of which 99 patients had congenital heart disease (CHD) [1]. Based on the available evidence from these studies, we concluded that CHD may increase the risk of poor outcomes for those who are contracting ; and yet due to limited cohort size and available data, there is a necessity for more research with larger sample sizes in order to have a more justified conclusion.…”
mentioning
confidence: 99%